The development of character category in Jawi typography-an implementation in typography course in UiTM / Intan Nur Firdaus Muhammad Fuad, Sharifah Raudzah S. Mahadi and Ahmad Khairul Azizi Ahmad - Muhammad Fuad, Intan Nur Firdaus; S. Mahadi, Sharifah Raudzah; Ahmad, Ahmad Khairul Azizi (2017)
The treasures inherited by Malays are the jawi texts that have been used for many years. The history of its use along with the arrival of Islam goes beyond hundreds of years. Historical discovery is an important proof of how jawi texts were used in many writing and art. Jawi's defense was finally collapsed and threatened when there was a 1963 Akta Bahasa which stipulated Rumi's writing into Malay, the purity of Jawi writing should be done to see this jawi writing continue to breathe. The use in the design field is also seen as not widely used by jawi calligraphy itself, also the jawi calligraphy symbols are not widely used as identity logos in companies in Malaysia despite the fact that the company belongs to the Malays themselves. As designers especially bumiputras there are lack of the master or practicer on jawi letters, Where jawi writing and jawi calligraphy are only exposed at school through several programs, including the J-QAF program. In the main objective of this study, improvement to facilitate the comprehension of jawi characters in recognizing jawi letters is that this typographic anatomical system is structured yet flexible system that able to help designer to achieve coherency in organizing jawi typeface. The anatomy forms the great foundation on the typeface layout. This is important to designer espeacially typographer or calligrapher to use it in every project to ensure that they are using the same level of quality and displaying consistenly of the end result in every each of jawi typeface exploration.